Organizacja wirtualna jako odpowiedź na realia gospodarcze XXI wieku - Mirowski, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The level of virtualization of economic life in European Union creates good conditions for virtual organizations to exist and develop. Accessibility of IT systems, growing share of services, provided via Internet, increase of technical self-consciousness in this subject and currently experienced global economy slowdown, increase the need to act in structures which are less expensive to maintain. New type of workers, who draw on their knowledge while working, fits to flexible types of organizations, which allow to fully use their potential and to create effective, knowledge based economy.
Keywords: organizacja wirtualna; gospodarka; realia; XXI wiek